Beyond size and shape: Physicochemical properties of microplastic test materials generated by cryomilling - Lucy Howarth-Forster; Robyn Barrett; Robert Clough; Lisbet Sørensen; Jack Allen; Chris Powell; Richard C. Thompson; Matthew Cole; Michael Wilde (Journal of Hazardous Materials, 2026)

Deep dive into the chronic toxicity of tyre particle mixtures and their leachates - Paul Boisseaux; Cassandra Rauert; Pradeep Dewapriya; Marie-Laure Delignette-Muller; Robyn Barrett; Lee Durndell; Florian Pohl; Richard Thompson; Kevin V. Thomas; Tamara Galloway (Journal of Hazardous Materials, 2024)

Drift in the tropics: Phylogenetics and biogeographical patterns in Combretaceae - Olivier Maurin; Artemis Anest; Félix Forest; Ian Turner; Russell L. Barrett; Robyn C. Cowan; Lijia Wang; Kyle W. Tomlinson; Tristan Charles‐Dominique (Global Ecology and Biogeography, 2023)
Aim The aim of this study was to further advance our understanding of the species‐rich, and ecologically important angiosperm family Combretaceae to provide new insights into their evolutionary history. We assessed phylogenetic relationships in the family using target capture data and produced a dated phylogenetic tree to assess fruit dispersal modes and patterns of distribution. Location Tropical and subtropical regions. Time Period Cretaceous to present. Major Taxa Studied Family Combretaceae is a member of the rosid clade and comprises 10 genera and more than 500 species, predominantly assigned to genera Combretum and Terminalia , and occurring on all continents and in a wide range of ecosystems. Methods We use a target capture approach and the Angiosperms353 universal probes to reconstruct a robust dated phylogenetic tree for the family. This phylogenetic framework, combined with seed dispersal traits, biome data and biogeographic ranges, allows the reconstruction of the biogeographical history of the group. Results Ancestral range reconstructions suggest a Gondwanan origin (Africa/South America), with several intercontinental dispersals within the family and few transitions between biomes. Relative abundance of fruit dispersal types differed by both continent and biome. However, intercontinental colonizations were only significantly enhanced by water dispersal (drift fruit), and there was no evidence that seed dispersal modes influenced biome shifts. Main Conclusions Our analysis reveals a paradox as drift fruit greatly enhanced dispersal distances at intercontinental scale but did not affect the strong biome conservatism observed.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Thermoregulatory plasticity in free-ranging vervet monkeys, Chlorocebus pygerythrus - Alwyn Lubbe; Robyn S. Hetem; Richard McFarland; Louise Barrett; Peter S. Henzi; Duncan Mitchell; Leith C. R. Meyer; Shane K. Maloney; Andrea Fuller (Journal of Comparative Physiology B, 2014)